A systematic review of qualitative studies examining barriers and facilitators to orthopaedic surgeon engagement with patient-reported outcome measures data - Emma L. Heath; Ian A. Harris; Lorena Romero; Ilana N. Ackerman (Journal of Patient-Reported Outcomes)
Abstract Background Orthopaedic surgeon engagement with patient-reported outcome measures (PROMs) data has not been comprehensively evaluated, despite increasing uptake of orthopaedic PROMs programmes globally. The aim of this review was to systematically identify, appraise and synthesise qualitative evidence on barriers and facilitators to orthopaedic surgeons’ engagement with PROMs data and their use of these data to support clinical practice. Methods Six databases (MEDLINE, EMBASE, COCHRANE CENTRAL, PSYCINFO, CINAHL and EMCARE) were searched from January 2000—March 2024 to identify potentially eligible qualitative studies. Established systematic review methods were used for screening and data extraction, applying PRISMA guidelines. Quality assessment was undertaken using the Joanna Briggs Institute tool for qualitative research. Results Eight studies were eligible for inclusion; of these, five studies were qualitative and three studies were mixed-method designs incorporating a qualitative component. Three studies were specific to orthopaedic surgeons and the remaining five studies comprised of mixed samples of health professionals including orthopaedic surgeons. Only one study was classified as being of high methodological quality. Key barrier themes for orthopaedic surgeons were logistical issues, difficulty interpreting and understanding PROMs, and scepticism of the value of PROMs in clinical care. Key enabler themes included improvements to PROMs infrastructure, surgeon education around the potential value, uses and interpretation of PROMs data, aggregate reporting of PROMs data and early involvement of surgeons in the planning and development of PROM systems. Conclusion While these studies highlight some practical considerations and opportunities that can be addressed through clinician education, there is little high-quality evidence on factors that influence orthopaedic surgeon engagement with PROMs data. Robust qualitative research is needed to better inform tailored support and assist surgeons in integrating PROMs data within orthopaedic care.